PENGARUH MEDIA SOSIAL TERHADAP KEMUNCULAN IDE BUNUH DIRI PADA REMAJA - Maharani, Salma Kartika; Hatini, Dyah Estuti Tri; Suyana, Suyana (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
Suicide is an act of taking one's life consciously and deliberately due to certain factors. Suicidal ideas arise due to mental health disorders and lack of social support. This research aims to reveal the causes of the suicide phenomenon which is said to have become a trend in recent years and the influence of social media on the emergence of suicidal ideas in teenagers. This research uses a literature study research method with a qualitative descriptive approach. The research results reveal that the phenomenon of suicide has increased in recent years. This is analyzed using Durkheim's theory which focuses on the increase in suicide rates and its relationship with the condition of society. Pressure from society and ideal standards make some individuals decide to commit suicide. Individuals who commit suicide must have suicidal ideas/thoughts. One of the factors that influences the emergence of suicide, especially in teenagers, is the intensity of using social media. The tendency of teenagers to use social media actively causes mental health problems. The existing ideal standards also make teenagers feel pressured, triggering feelings of anxiety, stress, and even depression. Teenagers' difficulty in managing emotions and deciding on solutions makes most of them have suicidal thoughts. This research concludes that (1) the term suicide trend emerged due to an increase in suicide cases caused by pressure from society (2) social media has an influence on the emergence of suicidal ideation in teenagers.